Tingkat Partisipasi Masyarakat Dalam Musyawarah Perencanaan Pembangunan Di Desa Maburai Kecamatan Murung Pudak Kabupaten Tabalong - Siti Arbayah; Heni Suparti (stiatabalong.ac.id, 2022)
Regional development planning is the implementation of community participatory development planning based on Law Number 25 of 2004 concerning the National Development Planning System (SPPN). Two approaches to development planning in the SPPN are top-down and bottom-up participatory development planning. Regional development planning by involving bottom-up communities is carried out with the musrenbang mechanism starting from the village, sub-district, district and provincial levels. At the village level, this deliberation is called the Village Development Planning Deliberation (Musrenbangdes). Musrenbangdes provides broad opportunities for village communities to participate in development planning and discuss problems faced and alternative solutions at the village level. This study aims to determine the power or degree of community participation in the implementation of the Maburai Village Development Planning Meeting, Murung Pudak District, Tabalong Regency. The method used by the researcher is descriptive quantitative, with the sampling technique that will be used in this study is non-random sampling (non-probability sampling), namely purposive sampling. The results showed that the level of community participation in the development planning deliberations in Maburai Village reached the sixth rung of the ladder, namely the Partnership ladder, or up to the degree of Community Power (citizen power). At the rung of the Partnership ladder, the community can negotiate with the policy makers, namely the village government. At this level, the community is not only given the space to have a voice, but also the power to make decisions.